A measuring method for the resonant frequency of flexural horn-type transducer using non-contacting piezoelectric sensor. (November 2020) - Zhang, Hang; Pei, Yong-Chen; Liu, Qin-Jian
Graphical abstract: Highlights: Resonant frequency of flexural horn-type transducer is measured and investigated. Resonant frequency measurement is made by a non-contacting piezoelectric sensor. Specialized testing system is developed to measure transducer resonant frequency. Resonant frequency measuring method is verified using the impedance circle method. Vibration energy spectrum of flexural horn-type transducer is discussed in detail. Abstract: Flexural horn-type transducer is widely applied in high-power ultrasonic field. In this paper, an acoustic emission (AE) sensor acts as a non-contacting piezoelectric sensor responding to the mechanical vibration generated by the flexural horn-type transducer, and the measurement is made using the non-contacting piezoelectric sensor near the output end of the flexural horn-type transducer. A test system including an AE sensor is developed and its composition and working process are illustrated in detail. For verifying the measuring accuracy of the developed system, the resonant frequency of flexural horn-type transducer is measured by the developed test system and an impedance analyzer, respectively. The results showed that the resonant frequency of the flexural horn-type transducer measured by the proposed measuring system is agree well with that of the impedance circle method, confirming the accuracy of the developed test system.